Allocating Resources among Prisons and Social Programs in the Battle against Crime - Donohue, John (The journal of legal studies, 1998)
This article evaluates the cost and crime-reducing potential of prisons and social spending, setting forth the conditions under which a shift in resources from an expanding prison population into social spending would lead to a reduction in total crime. Preschool enrichment programs coupled with family intervention have generated impressive results in reducing crime in a number of different studies. Targeting of resources toward those children most at risk of criminal behavior is necessary to generate cost-effective crime reduction, but this may be difficult to achieve because of political or constitutional constraints. Given precise targeting, and if a broadly implemented preschool program (more enriched than the current Head Start program) could generate half the crime-reduction benefits achieved in the pilot studies, then cutting spending on prisons and using the savings to fund intensive preschool education would reduce crime. The elasticity of crime with respect to incarceration is taken to be .15